Transesophageal endoscopic ultrasound in the diagnosis of the lung masses: a multicenter experience with fine-needle aspiration and fine-needle biopsy needles. Issue 7 (29th April 2022) - Mangiavillano, Benedetto; Spatola, Federica; Facciorusso, Antonio; De Nucci, Germana; Ligresti, Dario; Henry Eusebi, Leonardo; Lisotti, Andrea; Auriemma, Francesco; Lamonaca, Laura; Paduano, Danilo; Crinò, Stefano; Scarlata, Simone; et al.
Abstract : Background and aim: Intraparenchymal lung masses inaccessible through bronchoscopy or endobronchial ultrasound guidance pose a diagnostic challenge. Furthermore, some fragile or hypoxic patients may be poor candidates for transbronchial approaches. Endoscopic ultrasound-guided fine-needle aspiration/biopsy (EUS-FNA/FNB) offers a potential diagnostic approach to lung cancers adjacent to the esophagus. We aimed to evaluate the feasibility, accuracy, and safety of trans-esophageal EUS-FNA/FNB for tissue sampling of pulmonary nodules. Methods: We retrospectively analyzed data from patients with pulmonary lesions who underwent EUS-FNA/FNB between March 2015 and August 2021 at eight Italian endoscopic referral centers. Results: A total of 47 patients (36 male; mean age 64.47 ± 9.05 years) were included (22 EUS-FNAs and 25 EUS-FNBs). Overall diagnostic accuracy rate was 88.9% (76.3–96.2%). The sensitivity and diagnostic accuracy were superior for EUS FNB sampling versus EUS-FNA (100% vs. 78.73%); P = 0.05, and (100% vs. 78.57%); P = 0.05, respectively. Additionally, sample adequacy was superior for EUS-FNB sampling versus EUS-FNA (100% vs. 78.5%); P = 0.05. Multivariate logistic regression analysis for diagnostic accuracy showed nodule size at the cutoff of 15 mm (OR 2.29, 1.04–5.5, P = 0.05) and use of FNB needle (OR 4.33, 1.05–6.31, P = 0.05) as significant predictors of higher diagnostic accuracy. There were no procedure-related adverse events. Conclusion: This study highlights the efficacy and safety of EUS-FNA/FNB as a minimally invasive procedure for diagnosing and staging peri-esophageal parenchymal lung lesions. The diagnostic yield of EUS-FNB was superior to EUS-FNA.